Evaluating Anti-ESKAPE Potential of Valeriana Officinalis L. Extract against Healthcare-Associated Infections in Tertiary Hospitals of Al-Kharj Governorate: An In Vitro Study - Mohammed S. Khan; MD Nadeem Bari (Journal of Pharmacy and Bioallied Sciences)
Background: Healthcare-associated infections (HAIs) caused by ESKAPE pathogens are a significant concern in tertiary hospitals worldwide, including those in Al-Kharj, Saudi Arabia. This study aimed to explore the bioactive compounds from Valeriana officinalis and evaluate their antimicrobial activity against ESKAPE pathogens. Materials and Methods: Methanolic extracts of the Valeriana officinalis stem were prepared and subjected to phytochemical analysis, thin-layer chromatography (TLC), and antimicrobial testing using the well-diffusion method. The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and cytotoxicity (MTT assay) were also evaluated. Results: The extract contained several major phytochemicals with significant activity against ESKAPE pathogens. The MIC values were 50 mg/mL for Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa, 100 mg/mL for Enterococcus faecalis and Staphylococcus aureus, and 25 mg/mL for Escherichia coli. The MBC values were 25 mg/mL for Escherichia coli and 100 mg/mL for the other ESKAPE pathogens. Conclusion: The methanolic extract of Valeriana officinalis L. demonstrated potent antimicrobial activity, with relatively low MIC and MBC values against ESKAPE pathogens responsible for HAIs.